PENGARUH TEMPERATUR TUANG DAN KANDUNGAN SILICON TERHADAP NILAI KEKERASAN PADUAN Al-Si - Bahtiar, Bahtiar; Soemardji, Leo (Jurnal MEKANIKAL, 2012)
Research on the effect of temperature and silicon content cast on the value of Al-Si alloy violence done by re-casting of the alloy Al-0.24% Si. The temperature variation with temperature castings made ​​71, 760 and 810oC. The addition of silicon content is done by adding alloys Al-0.24% Si alloy ADC 12. From the results of the study concluded that the temperature did not cast a significant influence on increasing the value of violence. Effect of the addition of silicon content increases the value of the product of violence cast Al-0, 24Si at 33.67 to 56.06 BHN on silicon content of 2.66% for a temperature of 710oC cast. Hardness value at a temperature of 760OC castings for silicon content of 0.24% by 34.59 BHN also experienced an increase in the silicon content of 2.66% to 50.81 BHN hardness value. BHN hardness value of 36.55 at a temperature of 810 OC cast for the silicon content of 0.24% increased to 54.24 BHN on silicon content of 2.66%.